Navigating Human Resource Capacity and Accountability Challenges in Decentralized Public Finance: A Qualitative Meta-Synthesis - Rabiyatul Jasiyah; Suriadi Suriadi (Fundamental and Applied Management Journal, 2026)
This study aims to analyze and synthesize prior research on navigating human resource capacity and accountability challenges in decentralized public finance through a Systematic Literature Review (SLR). The review focuses on how human resource capacity, fiscal autonomy, digital governance, and accountability mechanisms interact in shaping the effectiveness of decentralized public financial management. The SLR method was employed because it allows a structured and transparent synthesis of previous findings, identifies recurring patterns, and clarifies inconsistencies across studies. Literature was searched through the Directory of Open Access Journals (DOAJ), covering publications from 2022 to 2026, using combinations of keywords related to fiscal decentralization, human resource capacity, accountability, transparency, local government finance, and public financial management. The initial search identified 63 records, which were then screened based on title relevance, abstract suitability, research focus, publication year, full-text availability, and substantive alignment with the topic. After the selection process, 11 articles were retained for final review and analyzed through descriptive-qualitative synthesis. The findings indicate that decentralized public finance becomes more effective when supported by competent human resources, merit-based administration, strong internal control, adequate digital systems, and meaningful citizen participation. In contrast, weak technical capacity, fiscal dependence, fragmented institutions, and limited managerial autonomy repeatedly hinder accountability outcomes. This review contributes to the literature by reinforcing the capacity–accountability linkage as a central explanatory framework and by offering practical insight for policymakers and public administrators seeking to strengthen local fiscal governance in decentralized settings.